“HA CORRIDO ESTA FAMA Y COMO ANDABA HUYENDO DE LA JUSTICIA, TODO CUANTO MALO SE HACÍA SE LE IMPUTABA". THE COMMUNITY OF LOS HORNOS DE ILLAPEL IN THE CASE OF RAMÓN CORTÉS, 1778-1783 - Girón Zúñiga, Nicolás (Revista de Historia Social y de las Mentalidades, 2024)
This article examines the case of a man named Ramon Cortés from a micro-historical perspective. From his judiciary record, the purpose is to know how the people of Los Hornos de Illapel were involved in the prosecution of the case. The aim is to analyze strategies of social production that took place in the framework of the judiciary practices in the eighteenth century in Chile. The work is part of what has been called "social history of justice", and contains a reflection on the community idea and the “publica voz y fama” formula. The author explains the differences in the understanding of public fame, from a social viewpoint and other judicial, linked to a mechanism of political representation by judiciary agents.